Leukocyte telomere length associates with nasopharyngeal carcinoma risk and survival in Hong Kong Chinese. Issue 9 (7th August 2018) - Ko, Josephine Mun‐Yee; Tsang, Kay Hiu‐Ki; Dai, Wei; Choi, Sheyne Sta Ana; Leong, Merrin Man‐Long; Ngan, Roger Kai‐Cheong; Kwong, Dora Lai‐Wan; Cheng, Ashley; Lee, Anne Wing‐Mui; Ng, Wai Tong; Tung, Stewart; Lee, Victor Ho‐Fun; et al.
Abstract : Telomere shortening occurs as an early event in tumorigenesis. The TERT‐CLPTM1L locus associates with nasopharyngeal carcinoma (NPC) risk. It remains unknown if leukocyte telomere length (LTL) associates with NPC risk and survival. The relative LTL (rLTL) was measured by quantitative‐PCR in 2, 996 individuals comprised of 1, 284 NPC cases and 1712 matched controls. The odds ratio (OR) and 95% confidence intervals (CI) were calculated by logistic regression. The hazard ratio (HR) and 95% CI were calculated by Cox regression for survival analysis with rLTL and other clinical parameters in 1, 243 NPC with a minimum follow‐up period of 25 months. NPC patients had significantly shorter telomere length than controls. Shorter rLTL significantly associated with increased NPC risk, when the individuals were dichotomized into long and short telomeres based on median‐split rLTL in the control group (OR = 2.317; 95% CI = 1.989–2.700, p  = 4.10 × 10 −27 ). We observed a significant dose–response association ( p trend  = 3.26 × 10 −34 ) between rLTL and NPC risk with OR being 3.555 (95% CI = 2.853–4.429) for the individuals in the first quartile (shortest) compared with normal individuals in the fourth quartile (longest). A multivariate Cox regression analysis adjusted by age demonstrated an independent effect of rLTL on NPC survival for late‐stage NPC patients, when the individuals were categorized into suboptimal rLTL versus the medium rLTL based on a threshold set from normal (HR = 1.471, 95% CI = 1.056–2.048, p  = 0.022). Shorter blood telomeres may be markers for higher susceptibility for NPC risk. Suboptimal rLTL may be a poor prognostic factor for advanced NPC patients, as it associates independently with poor survival. Abstract : What's new? Telomere length can contribute to age‐related diseases, including cancer. These authors measured telomere length in leukocytes to look for a relationship with nasopharyngeal carcinoma (NPC). Shorter telomeres, they found, associated with increased risk of NPC. Somewhat surprisingly, people with suboptimal telomere length, either shorter or longer than average, appeared to have increased risk of late‐stage disease and poorer survival. Measuring blood telomere length could provide a simple, non‐invasive prognostic test for NPC.